Evaluasi Kepuasan Pemustaka Terhadap Layanan Perpustakaan IPDN Kampus NTB: Studi Tahun 2025 - I Wayan Wijanaraga; I Ketut Bayu Pawana (UIN Mataram, 2025)
This study is motivated by the importance of evaluating user satisfaction as part of the effort to improve library service quality in higher education institutions, particularly at IPDN NTB Campus. In an era of governance that demands transparency and accountability, user satisfaction has become a key indicator within the internal quality assurance system (SPMI) and serves as a basis for formulating service development policies. The aim of this research is to measure the level of user satisfaction with the library services at IPDN NTB Campus in 2025, analyze trends in comparison with previous periods (2018, 2021, 2022, and 2024), and identify aspects that need improvement. The study employed a descriptive quantitative survey method using a questionnaire based on nine elements of public service standards issued by the Ministry of Administrative and Bureaucratic Reform (Kementerian PAN-RB), including procedures, requirements, service time, cost/tariffs, service products, staff competence, staff behavior, facilities/infrastructure, and complaint handling. Data were analyzed quantitatively to obtain the average User Satisfaction Index (IKP) score for each element and its trend over time. The results indicate that, overall, the library services at IPDN NTB Campus in 2025 are rated as excellent. Eight out of nine service elements showed an increase in score compared to previous periods, with the highest achievement in the cost/tariff element (3.8732) and the lowest in the facilities/infrastructure element (3.5915), which experienced a slight decrease from the previous year but remained in the “excellent” category. Longitudinal comparisons highlight continuous improvements in procedural aspects, service speed, librarian competence, and responsiveness to feedback. These findings confirm the effectiveness of the implemented service quality improvement strategies and provide an empirical basis for formulating action plans and developing more adaptive, innovative, and sustainable library services.